2009
DOI: 10.4049/jimmunol.0804384
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Migration of Human Dendritic Cells Are Regulated by an IFN-α-Inducible Axl/Gas6 Pathway

Abstract: Axl, a prototypic member of the transmembrane tyrosine kinase receptor family, is known to regulate innate immunity. In this study, we show that Axl expression is induced by IFN-α during human dendritic cell (DC) differentiation from monocytes (IFN/DC) and that constitutively Axl-negative, IL-4-differentiated DC (IL-4/DC) can be induced to up-regulate Axl by IFN-α. This effect is inhibited by TLR-dependent maturation stimuli such as LPS, poly(I:C), TLR7/8 ligand, and CD40L. LPS-induced Axl down-regulation on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 56 publications
7
69
0
3
Order By: Relevance
“…It is known that TAM receptors are differentially expressed in mature immune, nervous, reproductive, and vascular systems (11), and have different patterns of transcriptional regulation. For example, mammary epithelial cells express MER only in the involution stage, whereas AXL is up-regulated by IFN-␣ in dentritic cells (13,58). Moreover, it remains to be determined whether in cells that co-express more than one TAM receptor, the receptors can heterodimerize, and if so, how this affects ligand receptor interactions as well as post-receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that TAM receptors are differentially expressed in mature immune, nervous, reproductive, and vascular systems (11), and have different patterns of transcriptional regulation. For example, mammary epithelial cells express MER only in the involution stage, whereas AXL is up-regulated by IFN-␣ in dentritic cells (13,58). Moreover, it remains to be determined whether in cells that co-express more than one TAM receptor, the receptors can heterodimerize, and if so, how this affects ligand receptor interactions as well as post-receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It plays broad roles in cell survival and proliferation, cell adhesion and migration, the stability of coagulation, the release of inflammatory factors, and physiological and pathological reaction processes (Eng et al, 2008;Ganopolsky et al, 2008;Xiong et al, 2008;Anwar et al, 2009;Scutera et al, 2009;Uehara et al, 2009;Wu et al, 2011). Manfioletti et al (1993) suggested that the GAS6 protein contained 678 amino acids, with 81% homology to mouse protein and 44% homology to the human anticoagulant S protein (S protein is a negative regulator of blood, regulating the vitamin K-dependent pathway).…”
Section: Introductionmentioning
confidence: 99%
“…4 Models of endotoxemia also suggest an important role in modulation of the immune response. [4][5][8][9][10][11] Given the involvement of GAS6 receptors in experimental sepsis, and the potentially major role of leukocyte apoptosis in the pathophysiology of severe sepsis, previous clinical studies have focused on GAS6 in septic and non-septic critical care patients. 3,[6][7] As compared to healthy subjects, GAS6 levels were higher in critical care patients with one or several failing organs, the highest values being observed in patients with severe sepsis.…”
mentioning
confidence: 99%